Geoinformatics in health facility analysis - Rai, Praveen Kumar; Nathawat, M. S. (Springer, 2017)
This book demonstrates how GIS techniques and statistical methods can be used to emphasise the characteristics of population and its related variables, vis-à-vis care facilities and the status of vector borne diseases, as well as for malaria modeling. Concentrating on the Varanasi district of India, the main aim of the book is to determine and map the density areas of vector borne diseases using GIS techniques. The book explores how health GIS is an important sub-discipline of health science and medical geography, which is traditionally focused on the spatial aspects of disease ecology and health care facility analysis.